Activation of p38 mitogen‐activated protein kinase in ovalbumin and ozone‐induced mouse model of asthma. Issue 3 (4th November 2013) - Liang, Li; Li, Feng; Bao, Aihua; Zhang, Min; Chung, Kian Fan; Zhou, Xin
Abstract: Background and objective: Ozone exposure worsens the development of allergen‐induced asthma. The p38 mitogen‐activated protein kinase (MAPK) pathway plays an important role in the development of the inflammatory response, airway hyperresponsiveness (AHR) and airway remodelling. In this study, the role of the p38 MAPK pathway on the effects of chronic ozone exposure in ovalbumin (OVA)‐sensitized and ‐challenged mice was investigated. Methods: Mice were sensitized and challenged with OVA followed by ozone exposure. Dexamethasone (Dex) and SB239063, a p38 MAPK inhibitor, were used as preventive treatment. Results: Compared with OVA‐challenged mice, ozone exposure of OVA‐challenged mice led to enhanced recruitment of inflammatory cells in bronchoalveolar lavage fluid, increases in inflammation scores, collagen accumulation, bronchial wall thickness and messenger RNA levels of inflammatory cytokines, along with activation of p38 MAPK/HSP27 and downregulation of MAPK phosphatase‐1 (MKP‐1) in the lung tissue. Dex treatment partially attenuated lung inflammation, while the cotreatment of Dex and SB239063 effectively reduced lung inflammation, inhibited airway remodelling, inactivated p38 MAPK/HSP27 and upregulated MKP‐1 in the lung tissue. Conclusions: Ozone exposure aggravated airway inflammation, airway remodelling, activation of p38 MAPK and downregulation of MKP‐1 in OVA‐sensitized and ‐challenged mice, which was ineffectively controlled by corticosteroids. p38 MAPK activation is a likely pathway involved in corticosteroid insensitivity. Abstract : Ozone exposure of OVA‐challenged mice caused airway inflammation, airway remodelling, activation of p38 MAPK/HSP27 and downregulation of MKP‐1, which were ineffectively controlled by corticosteroids. Cotreatment with corticosteroids and the p38 MAPK inhibitor, SB239063, however, was more effective. This indicates a potential for a p38 MAPK inhibitor in the treatment of corticosteroid insensitivity in severe asthma.